Triple Coupled Ring‐Core Fiber with Dual Highly Dispersive Windows for Orbital Angular Momentum Mode. Issue 10 (28th June 2022) - Geng, Wenpu; Bao, Changjing; Zhang, Lin; Fang, Yuxi; Wang, Yingning; Wang, Zhi; Liu, Weiwei; Ren, Yongxiong; Pan, Zhongqi; Yue, Yang
Abstract : Orbital angular momentum (OAM) beams, featured by the helical phase front and doughnut intensity profile, have been demonstrating great potential for various applications. Ring‐core optical fiber is also experimentally proven to be an effective waveguide for OAM mode. In general, managing the chromatic dispersion in the optical fiber is important for a wide range of applications. In this article, a highly dispersive germanium‐doped ring‐core fiber with dual selectable operating windows for OAM mode is proposed. The proposed fiber consists of three concentric high‐refractive‐index germanium‐doped rings with different mole fractions. The chromatic dispersion of the OAM1, 1 mode in the ring fiber can be as low as −129 964 ps/(nm·km) at 1644.4 nm as the light launches into the fiber from the innermost ring and −270 017 ps/(nm·km) at 1651 nm as the light enters from the outermost ring. Furthermore, the effect of the geometrical and material parameters on chromatic dispersion for OAM1, 1 mode is investigated. When the parameters of the innermost and outermost rings are varied separately, the corresponding operation windows are changed independently. An extremely negative dispersion for the OAM1, 1 mode of −817 576 ps/(nm·km) can be achieved. This design can serve as a dispersive element in various OAM‐based optical fiber systems. Abstract : A Ge‐doped ring‐core fiber with three concentric high‐index rings is proposed to achieve ultra‐large negative dispersion with dual selectable operating windows. This design can realize a negative dispersion down to −129 964 ps/(nm·km) for orbital angular momentum (OAM1, 1 ) mode with the launching location at the innermost ring and −270 017 ps/(nm·km) as the mode is excited from the outermost ring.